Notas sobre el género Gyrocarpus (Hernandiaceae) en México; un nombre nuevo: Gyrocarpus mocinnoi Espejo - Espejo Serna, Adolfo (Instituto de Ecología, A.C., 1991)
The nomenclatural and taxonomic status of Gyrocarpus americanus Jacq., G. jatrophifolius Domin and G. mocinnoi Espejo nom. et stat. nov. are clarified. Commentaries are made about the phenology of the species and a distribution map of the Mexican species is presented.